Near-infrared in situ generation of the higher-energy trans conformer of tribromoacetic acid: Observation of a large-scale matrix-site changing mediated by conformational conversion - Apostolo, Rui F. G.; Bazso, Gabor; Tarczay, Gyorgy; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Amer Inst Physics, 1305 Walt Whitman Rd, Ste 300, Melville, Ny 11747-4501 USA, 2018)
The first observation of the higher-energy conformer of tribromoacetic acid (trans-TBAA) is reported. The conformer was produced in cryogenic matrices (Ar, Kr, and N-2) by in situ selective narrowband near-infrared excitation of the lower-energy cis-TBAA conformer and characterized both structurally and vibrationally. The novel trans-TBAA conformer is shown to spontaneously decay to the most stable cis-TBAA form in all studied matrix media, by tunneling, and the measured decay rates in the different matrices were compared with those of the trans conformers of other carboxylic acids in similar experimental conditions. In the N-2 matrix, where trans-TBAA establishes a specific stabilizing intermolecular interaction with the host N-2 molecules via its OH group and is about 11 times more stable than in rare gas matrices, the effect of changing the irradiation wavenumber within the 2 nu OH absorption profile was investigated in detail. An interesting phenomenon of matrix-site changing mediated by conformational conversion was observed in the N-2 matrix: vibrational excitation of cis-TBAA in the 2 nu OH wavenumber range predominantly converts the molecules located in a specific "matrix site" into trans-TBAA; then, relaxation (by tunneling) of the produced higher-energy conformer back to the cis form populates almost exclusively another "matrix site." The experimental studies received support from quantum chemistry calculations, which allowed a detailed characterization of the relevant regions of the potential energy surface of the molecule and the detailed assignment of the infrared spectra of the two conformers in the various matrices. Published by AIP Publishing.
Keywords: Correlated Molecular Calculations; 1St Experimental-Observation; Disinfection By-Products; Gaussian-Basis Sets; Trifluoroacetic-Acid; Drinking-Water; Formic-Acid; Acetic-Acid; Vibrational Spectroscopy; Rotational-Isomerism